The impact of laparoscopic surgery on the symptoms and wellbeing of patients with deep infiltrating endometriosis and bowel involvement - Rogério Serafim Parra; Marley Ribeiro Feitosa; Hugo Parra de Camargo; Fernando Passador Valério; José Vitor Cabral Zanardi; José Joaquim Ribeiro da Rocha; Omar Féres (Taylor & Francis Group, 2021)
Background The purpose of this study was to evaluate the symptoms and wellbeing of patients who underwent laparoscopic colorectal resection for deep endometriosis infiltrating the rectum and/or colon in a single reference center. Methods We conducted a cross-sectional survey based on a structured questionnaire. All patients underwent laparoscopic discoid resection, segmental resection or shaving for deep endometriosis in a single reference center between October 2014 and October 2019. The following topics were addressed: symptoms related to endometriosis, fertility, disease recurrence and quality of life. The Institutional Review Board approved the study and signed informed consent was required before enrollment. Results A total of 77 of 160 (48.1%) subjects agreed to answer the questionnaire and were enrolled in the study. The mean age was 36.4 years (range, 24-54 years), and 45.5% of the patients had previously undergone surgery for deep endometriosis. Complete resolution of abdominal pain was observed in 48.1% of subjects after surgery. Pelvic pain was rated on a scale of 0 (no pain) to 10 (worst pain) before and after the procedure. In this evaluation, mean pain scores were reduced after surgery (9.21 ± 1.53 × 3.99 ± 3.14; p < .001). Other positive aspects reported by interviewees were increased willingness to perform daily activities (66.2%), increased physical activity (70.1%), better work performance (72.7%), improved dyspareunia (77.9%) and increased sexual activity (71.4%). Some negative aspects reported after surgery were straining at stool (35.1%), nocturia (24.7%), liquid-feces incontinence (13%), mild urinary incontinence (13%), urinary urgency (11.7%) and flatus incontinence (7.8%). Regarding pregnancy, 59% of patients tried to conceive after surgery, and the success rate was 28.2% (46.2% spontaneous and 53.8% after in vitro fertilization or insemination). Conclusions Laparoscopic surgery was associated with pain reduction and improved general wellbeing in patients diagnosed with deep endometriosis and bowel involvement.